Letter - Meyer, J.
021-0099-001 St. Ermins Restaurant Telephone WHITEHALL 3176 Telegraph ERMINITES LONDON ST. JAMES PARK LONDON. S.W.1 25th February, 1937 Ernest Bell Esq., Trades Union Congress., Transport House, SW.1. Dear Sir, In response to your kind enquiry this afternoon, I now have much pleasure in submitting specimen Menus at 4/6d and 5/- per head respectively, for the Luncheon Party you propose holding on Thursday, the 11th March next. I shall be pleased to make any reasonable alteration you may desire in either of these menus. It is noted that the party would number from 120 to about 200. Trusting to have the pleasure of catering for you and assuring you of every attention to your requirements. Yours faithfully, FOR ST. ERMIN'S RESTAURANT J. Meyer Manager Encs.- 292/946/21/99